The relation between self-reported educational, professional, and personal experiences in mental health care and choosing to specialize in mental health for nursing students - Marit van Gijsel; Koen Westen; Pim Peeters (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: A large shortage of mental health nurses is noticeable worldwide. Mental health nursing has also shown to be less popular than other nursing fields at Avans University of Applied Sciences.Purpose: A better understanding of what influences choosing a minor in mental health for second-year bachelor of nursing students.Method: A quantitative survey-based method was used. The sample consisted of 177 second-year bachelor of nursing students.Results: Multiple linear regression showed four variables significantly correlated with the selection of a minor in mental health: students’ interest in mental health care, which teachers taught about mental health care, previous internships in mental health care, and students’ close relative’s experience with mental health issues.Conclusion: The data confirm that a minor in mental health is rarely chosen. Not all topics found in previous qualitative studies were found to correlate with choosing a mental health care minor. Some questions were poorly understood and excluded from analysis. Overall effect sizes were small.